2008
DOI: 10.1177/1059840544556677
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Noncycloplegic Autorefractor to Perform Vision Screening in Preschools

Abstract: Early detection and treatment of vision disorders in children are important to avoid lifelong visual impairment; however, preschool vision-screening rates are low. Traditional methods of screening lack the precision of objective tests and are difficult to administer in preschoolers. This study adopted a method using school nurses to conduct vision screening in preschoolers with a portable autorefractor. In addition, the effectiveness of the school nurse in conducting follow-up was evaluated. In a sample of 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Our referral rate (27%) is both greater and less than that found in other reported programs. 3,11,12 Because automated screeners detect risk factors for amblyopia even prior to the development of pathology, this rate of referral is not unexpected. 13 Adjustments in the referral criteria in this age group have been recommended in an effort to lower referral rates and improve the PPV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our referral rate (27%) is both greater and less than that found in other reported programs. 3,11,12 Because automated screeners detect risk factors for amblyopia even prior to the development of pathology, this rate of referral is not unexpected. 13 Adjustments in the referral criteria in this age group have been recommended in an effort to lower referral rates and improve the PPV.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to examine 56% of children referred by providing in-school examinations with direct involvement of the school nurse, which is an improvement on other reported follow-up rates. 3,11 This rate has increased to 75% for the 2013 to 2014 school year by sending the information brochure/consent home early in the school year with follow-up by the nurse. In addition, because the entire process was completed at school, the students received the enthusiastic encouragement of the entire team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Traditional vision screening methods rely on assessments from experts based on screening techniques are supporting vision tests. These techniques include picture tests (eg, tumbling ‘E’, Bailey–Lovie chart, Sloan letter (ETDRS) test, or Landolt’s Broken Ring chart for distance visual acuity), 7 8 Ishihara test for colour vision 9 and stereo fly test for binocular vision disorders. 10 The methodologies to perform vision screening or diagnosis of vision problems require a high level of vision expertise, and a test battery.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Comparisons of hand-held autorefractors with table mounted autorefractors and portable power refractors have also been reported in the literature. 3136 The investigators of the Vision in Preschoolers Study and others have previously reported on comparisons of the hand-held Refractometer Retinomax (“Retinomax”; Nikon - Chiyoda-ku, Tokyo) and SureSight ™ Vision Screener (“SureSight”; WelchAllyn - Skaneateles Falls, NY) for detecting vision disorders in preschool children. 3234 A third autorefractor, the Palm-Automatic Refractometer (Palm-AR; Marco – Jacksonville, FL), is commercially available and offers many of the same features; however, there have been no reports published regarding its performance in preschool vision screening.…”
mentioning
confidence: 99%